Artha Budha Hospital Service System Using Laravel Livewire for Improved Operational Efficiency - Riska Amalia Praptiwi; Suaidah Suaidah; I Gede Arya; Debby Alita (Jurnal Pepadun, 2025)
The rapid advancement of digital technologies has driven significant changes in healthcare services, prompting hospitals to modernize their systems to improve patient care and operational efficiency. This study presents the development and implementation of a web-based digital service system at Artha Budha Hospital, utilizing the Laravel Livewire framework. The system aims to streamline key processes such as patient registration, appointment scheduling, real-time queue management, and electronic medical record (EMR) management, enhancing both administrative workflows and patient experiences. A case study approach was employed to assess the system’s functionality, followed by black-box testing to evaluate its core features. The results demonstrated that the system successfully reduced manual errors, increased operational efficiency, and improved data accuracy, while providing more transparent and responsive service to patients. The findings suggest that the digital service system not only supports the hospital’s operational needs but also contributes to digital transformation in healthcare, offering valuable insights into the effective integration of technology in hospital management.